Development of Precission Farming Hydropoonic Model Based On Internet of Things Using Arduino - Budi Tjahjono; Kundang Karsono; Lista Meria (International Journal of Science, Technology & Management, 2021)
Agricultural land in urban areas was needed for community food security. Narrow agricultural land posed obstacles in the implementation of urban agriculture. Hydroponi is a solution for agricultureal development on narrow land. Precesion farming was needed to maintain plant growth. Hydroponic system required regulation of air and water temperature, humidity, water level, pH, water nutrient. This study used SDLC methodology. The result of this research is an automatic hydroponic implementation that can monitor and control an Internet of Things based hydroponic system using Arduino.